2010
DOI: 10.1186/1475-2875-9-75
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of Plasmodium vivax dhfr and dhps mutations in isolates from Afghanistan

Abstract: BackgroundAnalysis of dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) mutations in Plasmodium vivax wild isolates has been considered to be a valuable molecular approach for mapping resistance to sulphadoxine-pyrimethamine (SP). The present study investigates the frequency of SNPs-haplotypes in the dhfr and dhps genes in P. vivax clinical isolates circulating in two malaria endemic areas in Afghanistan.MethodsP. vivax clinical isolates (n = 171) were collected in two different malaria endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
10
17
1
Order By: Relevance
“…In comparison with the current survey, highly mutant alleles were reported from Thailand, Vanuatu, Indonesia, and Papua New Guinea. In line with previous studies, in this study haplotypes with double mutations at FRTN were also found in Sistan and Baluchistan isolates, which was almost similar to that of obtained data from malarial endemic areas, such as Afghanistan and Pakistan (16,25). Moreover, the distribution frequency of these haplotypes was not much different from previous studies (12).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In comparison with the current survey, highly mutant alleles were reported from Thailand, Vanuatu, Indonesia, and Papua New Guinea. In line with previous studies, in this study haplotypes with double mutations at FRTN were also found in Sistan and Baluchistan isolates, which was almost similar to that of obtained data from malarial endemic areas, such as Afghanistan and Pakistan (16,25). Moreover, the distribution frequency of these haplotypes was not much different from previous studies (12).…”
Section: Discussionsupporting
confidence: 92%
“…The wild-type pvdhfr haplotype was present with a high percentage of P. vivax populations from this province. This was similar to reports from malaria endemic regions in Afghanistan (25) and Pakistan (26). In this study, the frequency of mutation in codon 58 (12.8%) and 117 (35.8%) was similar to the author's previous study (12).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the recent WHO report, about half of the world's population is at risk of malaria, and an estimated 250 million cases led to nearly 1 million deaths in 2006 [5]. Among them, Pakistan is also endemic for both P. vivax, and P. falciparum associated malaria infections [6,14,15].…”
Section: Resultsmentioning
confidence: 99%